VARIABEL-VARIABEL YANG BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN SERTA HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Cecilia Triana Dewi Lestari Embara (Faculty of Economics and Business Udayana University, 2012)
This study aims to determine the effect Institusional Ownership, Investment Opportunity Set, Free Cash Flow of Dividend Policy and to determine the influence of Institutional Ownership, Investment Opportunity Set, Free Cash Flow and Dividend influence on Stock Price. Population in this research are all manufacturing companies that go public and listed on the Indonesia Stock Exchange (IDX) from 2006 until 2008. Method of determining the sample is done by purposive sampling. The results showed that: 1) Institutional Ownership significant positive impact on Dividend Policy; 2) Investment Opportunity Set no significant effect on Dividend Policy; 3) Free Cash Flow a significant positive impact on Dividend Policy; 4) Institutional Ownership does not significantly affect the Share Price ; 5) Investment Opportunity Set a significant positive impact on Share Price; 6) Free Cash Flow is not a significant effect on stock prices; and 7) Dividends not significantly affect the stock price.